2006
DOI: 10.1590/s0103-50532006000400013
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of some hydrazones bearing the quinoline ring: potentiometric studies

Abstract: Três hidrazonas (oxímica: MHQ, cetônica: BHQ e fenólica: AHQ) contendo o anel quinolínico foram preparadas e caracterizadas. As suas constantes de dissociação e as constantes de estabilidade dos seus complexos com alguns íons de metais de transição, lantanídeos e actinídeos foram determinadas potenciometricamente em dioxano-água 75% (v/v) a 303K. Adicionalmente, constantes de estabilidade de cobaloximas (complexos Co II -MHQ) foram determinadas a 303K em solvente-água 75% (v/v) (solvente= dioxano, isopropanol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…2-Hydrazino-4,6-dimethylquinoline (HQ) is prepared as described in our previous publication [17]. To an ethanolic solution of 2-hydrazino-4,6-dimethylquinoline (HQ) (0.01 mol), o-anizaldehyde or o-hydroxyacetophenone (0.012 mol) was added.…”
Section: Preparation Of the Hydrazonesmentioning
confidence: 99%
See 1 more Smart Citation
“…2-Hydrazino-4,6-dimethylquinoline (HQ) is prepared as described in our previous publication [17]. To an ethanolic solution of 2-hydrazino-4,6-dimethylquinoline (HQ) (0.01 mol), o-anizaldehyde or o-hydroxyacetophenone (0.012 mol) was added.…”
Section: Preparation Of the Hydrazonesmentioning
confidence: 99%
“…They have pharmacological activities including antimicrobial, antioxidant, toxicity assessment [12], antiplasmodial, antimalarial [13], antituberculosis [14], anti-inflammatory [15] and anticancer properties [16]. This work is extension of studies on quinolone hydrazones [17][18][19][20][21][22][23][24]. The aim of the pH-metric studies is calculation of the dissociation constants of the ligands and the stability constants of their metal complexes in Egyptian Journal of Chemistry http://ejchem.journals.ekb.eg/…”
Section: Introductionmentioning
confidence: 99%
“…Seleem et al (2006) and others (Fazary et al, 2006) reported the effect of the reaction medium on protonation equilibria of different ligands. Different researchers have explained the effect of electrostatic and non electrostatic forces of interaction on different cosolvent-water mixtures that resulted in variation in the values of protonation constants of ligands or change in free energy (Pedada et al, 2009).…”
Section: Effect Of Solventmentioning
confidence: 99%
“…The cation stabilising nature of co-solvent, the composition of the solution, specific solvent-water interactions, solvation power, donor number, acceptor number, charge dispersion and specific interactions of co-solvent with solute account for little deviation from the linear relationship (Seleem et al, 2006).…”
Section: Effect Of Solventmentioning
confidence: 99%
“…These compounds can display antitubercular effects, based on their tendency to form metal chelates with transition metal ions. The complexes of 2-substituted phenyl hydrazone ligands with divalent transition and tetravalent lanthanides metal ions in solution and in solid states have been extensively studied in our laboratory (1)(2)(3) as examples, but little are reported with UO 2 (II) and Th (IV) ions (4)(5)(6) .…”
mentioning
confidence: 99%